Investing Back Home : Return Migration and Business Ownership in Albania - Kilic, Talip; Carletto, Calogero; Davis, Benjamin; Zezza, Alberto (World Bank, Washington, DC, 2012)
In view of its increasing importance, and the dearth of information on return migration and its impacts on source households, this study uses data from the 2005 Albania Living Standards Measurement Study survey and assesses the impact of past migration experience of Albanian households on non-farm business ownership through instrumental variables regression techniques. Moreover, considering the differences in earning potentials and opportunities for skill acquisition in different destination countries, the impact of household past migration experience is differentiated by main migrant destinations, namely Greece and Italy. The study also tests for the hypothesis of the existence of migration cycles, by differentiating the time spent abroad based on the year of return. The empirical results indicate that household past migration experience exerts a positive impact on the probability of owning a non-farm business. While one additional year in Greece increases the probability of household business ownership by roughly 7 percent, a similar experience in Italy or further destinations raises the probability by over 30 percent. Although past migration experience for the period 1990-2000 is positively associated with the likelihood of owning a household enterprise, a similar impact does not materialize for the period 2001-2004. The latter finding seems suggestive of the fact that more recent migrants are yet to attain a target level of required savings and skills in order to successfully establish a new business upon return.